The Substantial Difference Between USA and EU Welfare (European Journal of Marketing and Economics, 2024)
This comparative study explores the substantial differences in nonprofit organizations (NPOs) between the United States and Europe, examining their historical origins, operational frameworks, and roles within distinct welfare models. By analyzing the socio-economic contexts of liberal, corporatist-conservative, and social-democratic welfare systems, the research highlights how cultural, political, and economic factors shape the development and functioning of NPOs in different regions. The study reveals contrasting approaches to nonprofit sustainability, tax policies, and social service provision, with the U.S. model emphasizing market-driven efficiency and individual responsibility, while European models prioritize universal access, solidarity, and collaborative welfare provision. Through a comprehensive examination of organizational structures, funding mechanisms, and societal contributions, the research illuminates the unique characteristics of nonprofit sectors in these regions and proposes future research directions for measuring their economic and social impact.
Keywords: nonprofit organizations, welfare models, comparative nonprofit sector, social economy, welfare capitalism, third sector, civil society, social welfare, nonprofit sustainability, philanthropic strategies